2017
DOI: 10.1177/1010428317713389
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor–interacting protein 3a inhibits ovarian carcinoma metastasis via the extracellular HMGA2-mediated ERK/EMT pathway

Abstract: Local migration and long-distance metastasis is the main reason for higher mortality of ovarian cancer. Microtubule-associated tumor suppressor 1/angiotensin II type 2 receptor-interacting protein is associated with tumor initiation and progression and exerts anti-tumor effects. High mobility group AT-hook 2 is overexpressed in majority of metastatic carcinomas, which contributes to carcinomas metastasis through Snail-induced epithelial-to-mesenchymal transition signal pathway. The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…The function of ATIP1 as a TSG in glioma is substantiated by our observation that in glioma cells, elevated ATIP1 expression mitigates proliferation and clonogenic outgrowth as well as migration and invasion ( Figure 3 a–f) as has been demonstrated for several other tumors [ 31 , 32 , 33 ]. ATIP1 dramatically reduced glioma cell motility and enhanced cell adhesion at least partially by the construction of LFACs ( Figure 3 e,f).…”
Section: Discussionsupporting
confidence: 71%
“…The function of ATIP1 as a TSG in glioma is substantiated by our observation that in glioma cells, elevated ATIP1 expression mitigates proliferation and clonogenic outgrowth as well as migration and invasion ( Figure 3 a–f) as has been demonstrated for several other tumors [ 31 , 32 , 33 ]. ATIP1 dramatically reduced glioma cell motility and enhanced cell adhesion at least partially by the construction of LFACs ( Figure 3 e,f).…”
Section: Discussionsupporting
confidence: 71%
“…ATIP3a is involved extracellular signal-regulated kinase (ERK) and epithelial-to-mesenchymal transition (EMT). Reconstitution of ATIP3 inhibits tumor growth, which led to an increase in survival rate in ovarian carcinoma via down-regulation of the ERK/EMT pathway [ 27 ]. When MTUS1/ATIP3 expression was restored, ATIP3 changed the velocity of cell division by prolonged metaphase, thereby leading to a reduced number of proliferative cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ping et al noticed similar effect of AT2R in ovarian carcinoma. AT2R-interacting protein 3a blocked ovarian carcinoma migration and invasion by regulation of the ERK/EMT pathway [112]. In colorectal cancer, Ang II enhanced cell migration, however this effect was suppressed by AT1R and AT2R inhibitors [210].…”
Section: Angiotensins Have An Impact On Invasion and Metastasismentioning
confidence: 97%
“…Oh et al observed that in the xenograft model of breast cancer overexpression of AT1R was correlated with acceleration of tumor growth and increased expression of proliferation marker protein Ki67 (MKI67) [2]. In ovarian cancer, AT2R-interacting protein 3a inhibited proliferation of cells [112].…”
Section: Breast Cancermentioning
confidence: 99%